The ambiguity of artificial intelligence in scientific production (Revista Científica Integrada, 2023)
We live in a time of many questions that seem not to keep up with the speed at which artificial intelligence (AI) is developing. The advances are immense and surprising, putting human beings in confrontation with themselves, sometimes not being sure if they really are advances and placing them in a certain place of vulnerability in the face of the risks and threats that, supposedly, AI could represent. . It calls for the good use of AI, but what would that be? In this editorial, psychologist Lucas Bloc brings a path between challenge and avant-garde for science.
Keywords: Science; Technology; Artificial intelligence